Building Accounting and Entrepreneurship Skills in Orphanage Children - Andi Hamzah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Orphanages have an important role in providing protection and education for children in need. However, they often face challenges in preparing children for the real world after they leave the orphanage. Accounting and entrepreneurship skills are important aspects in equipping children with the ability to manage finances and develop their business potential. This service aims to help orphanage children develop basic accounting skills and a basic understanding of entrepreneurship. We strive to provide them with a foundation of knowledge that will assist them in managing their personal finances and open up opportunities to grow their business in the future. This service activity is carried out through a series of interactive workshops which include a basic understanding of accounting, recording simple transactions, making simple financial reports, and introducing basic concepts of entrepreneurship. Workshops are held periodically over a period of time to ensure deep understanding and practical application by children. The results of this community service activity show an increase in the understanding of orphanage children about the basic principles of accounting and the concept of entrepreneurship. They can understand the importance of accurate financial records and the opportunities to develop small businesses in their surroundings. The participants showed great enthusiasm in following the workshop and actively participated in the discussions and practical exercises. This service activity succeeded in building basic accounting skills and knowledge of entrepreneurship in orphanage children. With this knowledge base, they have the potential to manage their finances more wisely and develop small businesses that can have a positive impact on their future. Thus, this approach has the potential to make a positive contribution in equipping orphanage children with relevant and useful skills.